URGENSI PEMBANGUNAN AGROINDUSTRI KELAPA SAWIT BERKELANJUTAN UNTUK MENGURANGI PEMANASAN GLOBAL - Wawan Kurniawan (JURNAL TEKNIK INDUSTRI, 2012)
This paper was done to learn about the urgency of sustainability in agroindustry palm oil development to reduce global warming. Nowadays global warming should reduce its bad influence to all of us. As part of role in creation of global warming, palm oil industry have to conduct sustainable development. Various tool can be implemented for reach it such as AMDAL, Ecolabelling, ISO 14000, cleaner production and Roundtable on Sustainable Palm Oil (RSPO). Conducting of sustainable agroindustry sustainability could maintain our environment sustainable with the ultimate goal to reduce global warming. could keep our environment sustainable which due to reduce global warming